Tuberculous Granuloma - T M Uma Maheswari; N Gnanasundaram (Wolters Kluwer Medknow Publications, 2011)
Tuberculosis is a chronic granulomatous disease caused by Mycobacterium tuberculosis. There are two forms namely primary and secondary tuberculosis. Pulmonary tuberculosis is the most common form of primary tuberculosis. Primary tuberculosis in extrapulmonary site, though very uncommon, can occur in any site such as skin, brain, bone, eye, genitourinary tract and oral cavity. A 50-year-old male reported with complaint of swelling in the left maxillary region for 3 months duration. Intraorally diffuse firm swelling in the buccal mucosa with mild tenderness, free of secondary changes was present. Histhopathological report revealed Langhans' giant cell suggestive of tuberculous granuloma. This article emphasis the fact that primary oral tuberculosis should be considered as differential diagnosis of soft tissue swellings, as the communicable nature of the disease demands early diagnosis and treatment.